Pengaruh Aktivitas Fisik, Kesehatan Gizi, dan Kebugaran Jasmani Terhadap Hasil Belajar pada Pembelajaran Penjas - Nurlaela, Nurlaela; Komariah, Lilis; Rahmat, Alit (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to determine the effect of physical activity, nutritional health and physical fitness on learning outcomes in physical education learning. This research was conducted using the Systematic Literature Review (SLR) method. This research was also guided through several systematic review processes using PRISMA (Preferred Reporting items for Systematic Reviews and Meta-analyses). The database used to search for literature is available on Google Scholar. This research focuses on the influence of physical activity, nutritional health, and physical fitness on learning outcomes in physical education learning. Based on the results of the search carried out using a systematic literature review, there were 500 documents which then became 7 articles that were included in the criteria. Based on the research that has been carried out, the results of the research show a good relationship between physical activity and physical fitness levels, then the results of this research emphasize the importance of maintaining a balance between nutritional status and physical activity to achieve good physical fitness. Conclusion, the results of the research show that there is a relationship between nutritional status and physical activity. Keywords: Health Nutrition, Physical Activity, Physical Fitness, Physical Education Learning